2013
DOI: 10.1089/ten.tea.2012.0614
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Migration Affects Tissue-Engineered Cartilage Integration by Activating the Signal Transduction Pathways Involving Src, PLCγ1, and ERK1/2

Abstract: To determine the signal transduction pathways involved in chondrocyte migration and their effects on cartilage integration in autologous chondrocyte implantation. Articular chondrocytes were divided into three inhibitor groups pretreated with different inhibitors to Src, phospholipase Cγ1 (PLCγ1), and extracellular signal-regulated kinase (ERK)1/2 signaling pathways and one control group pretreated with vehicle. The effect of these pathways on chondrocyte migration was first explored by Boyden chamber assay, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
(27 reference statements)
3
18
0
Order By: Relevance
“…The average stress value in the regenerated cartilage, 158.0 ± 26.04 kPa, was more than 3 times higher than that reported in comparable studies . This may indicate that increased CPC migration enhanced tissue integration, which is consistent with the results in a study by Lu et al showing that cell migration at the interface of engineered cartilage and surrounding cartilage could result in dramatically stronger host–graft tissue integration after autologous chondrocyte implantation . It is also worth noting that the collagen fiber networks of the regenerated and host tissues in the fully treated defects were extensively entangled with each other, which might explain the gain in integration strength.…”
Section: Discussionsupporting
confidence: 86%
“…The average stress value in the regenerated cartilage, 158.0 ± 26.04 kPa, was more than 3 times higher than that reported in comparable studies . This may indicate that increased CPC migration enhanced tissue integration, which is consistent with the results in a study by Lu et al showing that cell migration at the interface of engineered cartilage and surrounding cartilage could result in dramatically stronger host–graft tissue integration after autologous chondrocyte implantation . It is also worth noting that the collagen fiber networks of the regenerated and host tissues in the fully treated defects were extensively entangled with each other, which might explain the gain in integration strength.…”
Section: Discussionsupporting
confidence: 86%
“…As one of the important signal molecules, ERK has been known to be involved in multiple signal pathways. Recent study showed that the Src-PLCγ1-ERK1/2 signaling transduction pathway is involved in cartilage tissue integration by affecting chondrocyte migration [ 23 ]. Here, our findings also indicated the existence of the PLCγ1/ERK axis in OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…PLCγ mediated FGFR3-induced STAT1 activation and this signaling cascade involved in the induction of apoptosis in the chondrogenic cell line ATDC5 [ 9 ]. The Src-PLCγ1-ERK1/2 signaling transduction pathway is involved in cartilage tissue integration by affecting chondrocyte migration [ 10 ]. Periodic mechanical stress also promotes chondrocyte proliferation and matrix synthesis in part through the Src-PLCγ1-MEK1/2-ERK1/2 signaling pathway [ 11 ].…”
Section: Introductionmentioning
confidence: 99%